A QUANTITATIVE ANALYSIS SHAPING ECONOMIC GROWTH IN PAKISTAN: INSIGHTS FROM STOCK MARKET PERFORMANCE (Contemporary Journal of Social Science Review, 2025)
The study evaluates the impact of Pakistan's stock market performance on its economic growth using econometric tools like Johansen Co-integration and a Vector Error Correction Model (VECM). The study uses quarterly time series data from Q1:2000 to Q2:2024 to establish a relationship. The industrial production index (IPI) is used as a proxy for economic growth, while other macroeconomic indicators like foreign direct investment (FDI), inflation (CPI), reserve money (M0), and the KSE-100 Index are used as predictors. The results show a long-term relationship between all variables, but a negative impact on long-term economic growth due to domestic industries' reluctance to compete with international ones. Reserve money has a positive long-term impact but a negative short-term impact. The Granger causality test confirms unidirectional causality between KSE-100 Index, M0, and IPI, but bidirectional causality exists between inflation and IPI. No causal relationship is found between FDI and IPI. The study recommends financial institutions to drive development in Pakistan.